MANFAAT DAN DAMPAK PERUBAHAN KEBIJAKAN JALUR ZONASI PADA PPDB 2020/2021 - Futum Hubaib; Maya Preva Biantary (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2022)
The purpose of this study was to determine the application, benefits and impacts of the zoning system policy in the New Student Admission (PPDB).The type of research used in this research is library research, namely research conducted based on books or literature, other reading materials to collect theories and concepts related to this research.The change to the Zoning Path Policy for the 2020/2021 Academic Year was made after studying various PPDB implementations in previous years at the local government level. Although the previous PPDB Permendikbud (Permendikbud No. 51 of 2018 and Permendikbud No. 20 of 2019) have been explicitly stipulated regarding each route, in its implementation the Regional Government makes PPDB provisions mainly on the zoning route with different mechanisms, even not according to the percentage minimum in the previous PPDB provisions.This PPDB regulation is designed so that regions can adjust the rules based on their characteristics and needsThe benefits of the school zoning policy in PPDB are equalizing access to education, bringing the school environment closer to the family environment, eliminating exclusivity and discrimination, assisting in the analysis of the calculation of teacher needs and their distribution, encouraging the creativity of teachers and local governments in providing assistance.Effective teachers are teachers who are able to use various strategies and approaches in teaching children with different abilities.